Circle hairs in a patient with multiple myeloma - Preeyachat Limtong (2022)
Circle hair is a rare body-hair disorder of unknown etiology, typically character-ized by perfectly or nearly perfectly coiled hair located below the cornified layer of the skin. Its main histopathological features are dilated hair-follicle infundibula and entrapped hair shafts. After its first description in 1963, there have only been a small number of reported cases, and its pathophysiology remains unclear. Herein, we report a case of an 80-year-old woman with skin lesions and abnormal hairs on both legs. We also propose a possible mechanism of her circle hairs: it may have occurred as an effect of her acquired ichthyosis secondary to her underlying multiple myeloma. There is no specific treatment for circle hairs, and reassurance that it is a harmless condition is sufficient. We prescribed a topical humec-tant and keratolytic agent to moisten the skin and lessen the hair entrapment, which resulted in clinical improvement. As the pathogenesis of the disease is unknown, further studies are warranted.